Compressive Strength of Concrete When Exposed to Elevated Temperature – A Review - Mustapa, Aishah Humairah; Abdul Hamid, Noor Azlina (Recent Trends in Civil Engineering and Built Environment, 2021)
Concrete is a composite material which is made of cement, aggregates and water. Fire resistance is one of the key considerations in concrete design. The exposure of high temperature such as fire incident will cause severe damage on physical and mechanical properties of concrete. Supplementary cementitious material (SCM) such as Fly Ash (FA) and Ground Granulated Blast Furnace Slag (GGBS) are widely used in construction industry as partial replacement in concrete. This study aims to review and compare the strength performance of concrete with different percentage of FA and GGBS replacement which exposed to high temperature. It was found that the incorporation of SCM has significant influence on concrete strength at high temperature. Incorporation of low percentage of FA (20%) and high percentage of GGBS (50%) showed favorable results in improving concrete residual compressive strength at high temperature compared to Ordinary Portland Cement (OPC) concrete.